NSGA-II Based Optimization of LLC Resonant Converter for 270V to 28V DC-DC Conversion in More Electric Aircraft - Kiymaz, Taha Yasin; Taskiran, Murat; Obdan, Atiye Hulya; Bekiroglu, Kamuran Nur (IEEE, 2025)
The increasing demand for More Electric Aircraft (MEA) has increased the need for efficient and compact power converters in aircraft power distribution systems. Although conventional Buck converters offer simplicity, they face limitations in aerospace applications due to efficiency constraints and thermal management challenges. To address these issues, this paper proposes a multi-objective optimized LLC resonant converter by NSGA-II method for 270V DC to 28V DC conversion in aerospace systems. The Pareto Frontier is used to visualize the optimization results to select the optimal design, and the accuracy of the optimized LLC converter is verified by simulations. The results show that the proposed converter meets the stringent requirements of modern aerospace applications, making it a promising alternative to conventional Buck converters for aerospace applications. For aerospace applications, an LLC converter design that can operate in the input voltage range of 250 V to 280 V DC and provide a 28 V DC output voltage with 280 W output power has been realized and verified by simulation studies.
Keywords: LLC; more electric aircraft (MEA); multi-objective optimization; NSGA-II; pareto-frontier; Computer Science; Robotics